Pengaruh Integritas, Objektivitas, Kompetensi, Perilaku Profesional dan Kerahasiaan Terhadap Kualitas Audit Dengan Independensi Sebagai Variabel Moderasi (Pada Kantor Inspektorat Kabupaten Jember) - Agrilia Priska Karismanda; Lia Rachmawati; Diana Dwi Astuti (JAKUMA : JURNAL AKUNTANSI DAN MANAJEMEN KEUANGAN, 2020)
The purpose of this study was to determine the effect of integrity, objectivity, competence, professional behavior and confidentiality on audit quality with independence as a moderating variable in the Inspectorate Jember office. The number of samples includes 30 people. The analytical method uses multiple linear regression, t test and moderation analysis with the classical assumption test research model, namely normality test, multicollinearity test, heteroscedasticity test. The results of this study state that objectivity partially affects audit quality, while integrity, competence, professional behavior and confidentiality do not partially affect audit quality. Independence can moderate the relationship between competence interactions with audit quality, while independence cannot moderate the relationship between interactions of integrity, objectivity, professional behavior and confidentiality on audit quality.